Pakistan : Request for an Extension of the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Pakistani authorities placed a request for a nine-month extension of the Stand-By Arrangement (SBA), to get sufficient time to complete the remaining fifth and sixth reviews under the SBA. The authorities believe that extending the arrangement will provide time to complete the reform of the general sales tax, implement measures to correct the course of fiscal policy, and amend the legislative framework for the financial sector. The IMF approved the extension, and emphasized to implement the IMF-supported program in accordance with the relevant IMF policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Pakistan